La circulación de los hombres y las técnicas. Reflexiones sobre la antropotecnología - Philippe Geslin (Universidade do Porto, 2012)
This text traces the milestones in the development of anthropotechnology since its beginings in 1962 until his recent institutionalization in Switzerland. It addresses the question of contingencies which prevail in its history, the networks of scientific and institutional support that facilitated its establishment in Switzerland. There is no anthropotechnology without fields of practices. Since the founding texts of Alain Wisner these fields are deeply transformed considering environmental constraints involved in policy and industrial development, thus opening up new avenues of action for our practices.